On the assessment of time-resolved diffraction results - Fournier, Bertrand (International Union of Crystallography, 2014)
Data collected during dynamic structure pump–probe crystallography experiments require appropriate indicators of agreement and tools to visualize the electron-density distribution changes. Agreement factors based on the ratio of intensities R with and without the external perturbation are shown to be analogous to the [Image: see text] (1) and w [Image: see text] (2) [Image: see text] factors widely used in standard crystallographic refinements. The η-based [Image: see text] factors, normalized by the average relative intensity change, are significantly larger than R-based values. It is shown that the relative intensity change η-based [Image: see text] factors are not suitable for comparing different data sets. Fourier photodifference maps allow the visualization of the externally induced structural changes in the crystal, but also can be used during refinement to observe residual peaks not yet accounted for by the model and thus monitor the progress of the refinement. The photodeformation maps are a complementary tool to confirm the validity of the final model. Photodeformation maps with equalized laser-on and laser-off thermal motion are used to highlight the structural changes.